2021
DOI: 10.3389/fphys.2021.718163
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Mechanisms Underlie Developmental Plasticity and Adult Acclimation of Thermogenic Capacity in High-Altitude Deer Mice

Abstract: Developmental plasticity can elicit phenotypic adjustments that help organisms cope with environmental change, but the relationship between developmental plasticity and plasticity in adult life (e.g., acclimation) remains unresolved. We sought to examine developmental plasticity and adult acclimation in response to hypoxia of aerobic capacity (V̇O2max) for thermogenesis in deer mice (Peromyscus maniculatus) native to high altitude. Deer mice were bred in captivity and exposed to normoxia or one of four hypoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 66 publications
(110 reference statements)
0
17
2
Order By: Relevance
“…First, the blood gas index of each group of rats was measured, because its changes can prove the hypoxia of the body and affect the pharmacokinetic characteristics of the drug ( Wang et al, 2016 ). Previous studies have shown that hypoxia increases hemoglobin levels in rats and cells ( Grek et al, 2011 ; Ivy et al, 2021 ). This study also found that acute hypoxia reduced SaO 2 , PaCO 2 , PaO 2 , and SBC, and increased Lac and Hb.…”
Section: Discussionmentioning
confidence: 99%
“…First, the blood gas index of each group of rats was measured, because its changes can prove the hypoxia of the body and affect the pharmacokinetic characteristics of the drug ( Wang et al, 2016 ). Previous studies have shown that hypoxia increases hemoglobin levels in rats and cells ( Grek et al, 2011 ; Ivy et al, 2021 ). This study also found that acute hypoxia reduced SaO 2 , PaCO 2 , PaO 2 , and SBC, and increased Lac and Hb.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of highland deer mice from the Rocky Mountains, Ivy et al (2021) found that exposure to hypoxia during early development improved both ventilation and whole-animal aerobic performance (cold-induced VO 2 max) during hypoxia in adulthood, and the magnitude of these improvements depended on the stage of developmental exposure. Normoxic controls were compared to mice exposed to hypoxia starting at three different life stages and extending into adulthood: life-long hypoxia (before conception to adulthood); post-natal hypoxia (birth to adulthood); and adult hypoxia (6-8 weeks only during adulthood).…”
Section: Introductionmentioning
confidence: 98%
“…The enhanced aerobic performance under hypoxia is associated with increased survivorship in free-ranging mice at high elevation (Hayes & O’Connor, 1999) and is associated with plastic and genetically based modifications across the oxygen transport cascade (Ivy & Scott, 2015; Schweizer et al, 2021, 2019; Storz & Cheviron, 2020; Storz et al, 2019; Storz & Scott, 2019). Research into the ontogeny of these differences has only just begun, but some components of the unique physiology of highlanders is clearly manifest within the first few weeks of life (Ivy et al, 2020; Ivy et al, 2021; Robertson et al, 2019; Velotta et al, 2020). The plastic responses to hypoxia also differ between highland and lowland mice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations